Lidocaine Infusion for the Management of Postoperative Pain and Delirium (LIMPP): protocol for a randomised control trial - Matthias Behrends; Marc Alan Buren; Alekos Theologis; Ariadne Zuraek; Aaron J Clark; Jacqueline M Leung (BMJ Open)
Introduction Postoperative delirium is a frequent adverse event following elective non-cardiac surgery. The occurrence of delirium increases the risk of functional impairment, placement to facilities other than home after discharge, cognitive impairment at discharge, as well as in-hospital and possibly long-term mortality. Unfortunately, there is a dearth of effective strategies to minimise the risk from modifiable risk factors, including postoperative pain control and the analgesic regimen. Use of potent opioids, currently the backbone of postoperative pain control, alters cognition and has been associated with an increased risk of postoperative delirium. Literature supports the intraoperative use of lidocaine infusions to decrease postoperative opioid requirements, however, whether the use of postoperative lidocaine infusions is associated with lower opioid requirements and subsequently a reduction in postoperative delirium has not been investigated.Methods and analysis The Lidocaine Infusion for the Management of Postoperative Pain and Delirium trial is a randomised, double-blinded study of a postoperative 48-hour infusion of lidocaine at 1.33 mg/kg/hour versus placebo in older patients undergoing major reconstructive spinal surgery at the University of California, San Francisco. Our primary outcome is incident delirium measured daily by the Confusion Assessment Method in the first three postoperative days. Secondary outcomes include delirium severity, changes in cognition, pain scores, opioid use, incidence of opioid related side effects and functional benefits including time to discharge and improved recovery from surgery. Lidocaine safety will be assessed with daily screening questionnaires and lidocaine plasma levels.Ethics and dissemination This study protocol has been approved by the ethics board at the University of California, San Francisco. The results of this study will be published in a peer-review journal and presented at national conferences as poster or oral presentations. Participants wishing to know the results of this study will be contacted directly on data publication.Trial registration number NCT05010148.